Effect of conservatim of intellectual capital (ex ante) and conservatism of earnings (ex post) on relevance of earnings - Sofian, Saudah (INSInet Publications, 2011)
This paper reviews the effect of both conservatism namely, conservatism of intellectual capital and conservatism of earnings on relevance of earnings. This paper shows that the decrease in the relevance of earnings is probably due to ex an te and ex post conservatism. Review of this paper suggests that researchers, practitioners, and accountants are required to seek and resolve this long standing issue by extending the horizon of research, which measures the role of conservatism of intellectual capital and conservatism of earnings. Therefore, this paper proposes a model that examines the effect of conservatism of intellectual capital (ex ante) and conservatism of earnings (ex post) on relevance of earnings.